Political status of non-Muslims in Islam: an alternative framework - Moniruzzaman, Md. (2021)
The classical Islamic minority laws known as the Dhimmah system are criticised as differentiated, discriminatory and at odd with the modern state system, which is based on the ideas of universal citizenship with equal socio-political, economic, and legal rights. This research argues that the theoretical framework of the classical Dhimmah system, which was based on Jizya and subjugation, was parochial and particularistic which requires fundamental revision. As opposed to that parochial and particularistic framework, this research offers a universalistic and integrated Islamic theory of non-Muslims’ political status in an Islamic state based on the Qur’anic model. The proposed framework integrates both the Islamic universal spirit and the citizenship model of the modern state system. The framework includes five elements, which are: one humanity (Muslims and non-Muslims), special qualified rights (for majority), qualified equal rights (for minority), minority particularities, and mutual respect. These five elements are justified by the Qur`anic prescriptions for inter-faith and inclusive social structure. The proposed universalistic framework demonstrates a greater potential of Islam to address modern political questions.